Specifics of the Mosaic Reflection Method of Elements of Ethnic Culture - Iurii A. Kuzmin (Publishing house "Sreda", 2020)
The article reveals the specifics of the methodology for studying ethnic elements of culture. The nomological paradigm of reflection of the socio-humanitarian sphere constituted the scientific status of ethno-cultural knowledge, at the same time leveling the subjective aspects, created a unification of forms and content, which inevitably led to a distortion of its actual parameters. As a tool for overcoming the imperfection of the classical principles of reflecting the phenomena of ethnic culture, they proposed a method of mosaic reconstruction that allows us to identify the relationship between elements of ethnic culture on the basis of common values. Mosaic reconstruction of ethnic culture reveals the logical relationship between its elements, forms of manifestation, and the totality of prerequisites and grounds. In a general sense, the method of mosaic reconstructions involves the following procedures, such as fixing specific ethnic elements of culture, creating a complex of links of ethnocultural integrity, determining the principles of interaction of system elements with the external and internal environment, applying the mechanism for restoring cultural integrity based on the principles of a cultural research program, visualizing a holistic image ethnic culture. The methodology of mosaic reconstruction is based on the fact that culture is the product of a social form of existence that expresses itself in the corresponding spheres of social activity, the restoration of which in its entirety is a necessary condition for creating an exhaustive image of culture. The author comes to the conclusion that mosaic reconstruction of ethnic culture reveals the logical relationship between its elements, forms of manifestation, and the totality of prerequisites and grounds.